The Influence of Authoritarian Leadership Style, Workplace Facilities, and Job Stress on Employee Performance at PT. Nidec Instruments Bekasi - Rismawati Rismawati; Daspar Daspar; Purwanti Purwanti; Dea Putri Meliyanti; Etty Zuliawati Zed (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to identify and analyze the influence of authoritarian leadership style, workplace facilities, and job stress on employee performance at PT Nidec Instruments Bekasi. Data were collected through questionnaires distributed to 86 employees of the company and analyzed using validity and reliability tests, classical assumption tests, the coefficient of determination, multiple linear regression, and hypothesis testing. The results reveal that authoritarian leadership style, workplace facilities, and job stress significantly affect employee performance. The coefficient of determination (R²) test indicates that 67.9% of the variation in employee performance is explained by the independent variables—authoritarian leadership style, workplace facilities, and job stress—while the remaining 32.1% is influenced by other factors not included in this research model. Furthermore, the F-test results show that these three variables, when examined simultaneously, have a positive and significant effect on employee performance, with an F-calculated value of 57.740, which is greater than the F-table value of 2.71.